PENGKAJIAN NILAI VEGETASI DATA MODIS DENGAN MENERAPKAN BEBERAPA ALGORITMA PENGOLAHAN DATA INDEKS VEGETASI - Indah Prasati (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2004)
The vegetation index (VI) that is extracted from MODIS data using several algorithms still needs to develop and to study. It is due to MODIS (Moderate Resolution Imaging Spectroradiometer) data that is relatively new in the operation and data application. The study aims to compare sensitivity application of 3 algorithms for extraction of vegetation index data. The simulation in this research is using MODIS data level 1B with all resolution (250m, 500m, and 1000m) for Kalimantan Island dated May 17, 2002 by applying NDVI algorithm (Normalized Difference Vegetation Index), SAVI (Soil Adjusted Vegetation Index),and SARVI (Soil and Atmosphere Resistant Vegetation Index). The result of this research shows that the application of SAVI and SARVI algorithms in cloud-dominated location will have higher vegetation index value as much as 0.001 - 0.04 unit with SAVI model, if compared with SAVI and can be higher or lower compared with SARVI value, depending on the condition of how much influential factor of atmospheric water vapor, aerosol content and canopy background that can be reduced and corrected by applying the SARVI model. In the meanwhile, in urban area, the applying of SAVI model will be lower as much as 0.14-0.15 unit, and about 0.1-0.15 unit with SARVI model if compared with NDVI.